Is Crocin Effective in Modulating Blood Lipid Levels? An Updated Systematic Review and Meta-Analysis with Dose– and Time–Response Assessments - Laurindo, Lucas Fornari; Chagas, Eduardo Federighi Baisi; Rodrigues, Victória Dogani; de Argollo Haber, Ricardo; Caracio, Flávia Cristina Castilho; Marangão, Maria Clara Capobianco; dos Santos Bueno, Manuela; de Souza Bastos Mazuqueli Pereira, Eliana; Detregiachi, Cláudia Rucco Penteado; Valenti, Vitor Engrácia [UNESP]; Cabrini, Mayara Longui; Barbalho, Sandra Maria (MDPI, 2025)
Background/Objectives: Dyslipidemia is a global health concern. It refers to increased blood levels of LDL-C, triglycerides, and total cholesterol, accompanied by decreased blood HDL-C levels. Many pharmacological and non-pharmacological approaches have been designed to improve dyslipidemia management. However, nutritional therapies have gained more attention due to their antioxidant and anti-inflammatory properties. In this scenario, the carotenoid crocin stands out as a prominent anti-dyslipidemia phytochemical. Its unique structure permits lipid-lowering effects via various mechanisms, including the enhancement of lipid breakdown, reduction in lipid formation, bolstering of antioxidant defenses to diminish lipid toxicity, and decreased absorption of dietary fats. However, no recent systematic review or meta-analysis has addressed its anti-dyslipidemia effects with statistical power. Therefore, we aim to fill this gap with our current meta-analysis, as well as dose and time–response assessments. Methods: PubMed, SpringerLink, ScienceDirect, Cochrane, and Google Scholar databases were searched, and PRISMA guidelines were followed. Ten studies comprising eleven results were included. Results: Crocin did not improve LDL-C (0.2120, 95% CI: −0.0799 to 0.5040), HDL-C (−0.1937, 95% CI: −0.4896 to 0.1022), triglyceride (−0.2063, 95% CI: −0.5764 to 0.1638), or total cholesterol (0.1528, 95% CI: −0.1074 to 0.4129). The dose–response or time–response was also not statistically significant. Conclusions: More clinical studies with robust designs must be conducted to thoroughly assess crocin’s effectiveness in modulating lipid levels with the utmost care.